Progress in microneedle array patch (MAP) for vaccine delivery - Nguyen, Thuy Trang (Hum Vaccin Immunother, 2020)
A microneedle array patch (MAP) has been developed as a new delivery system for vaccines. Preclinical and clinical trials with a vaccine MAP showed improved stability, safety, and immunological efficacy compared to conventional vaccine administration. Various vaccines can be delivered with a MAP. Currently, microneedle manufacturers can mass-produce pharmaceutical MAP and cosmetic MAP and this mass-production system can be adapted to produce a vaccine MAP. Clinical trials with a vaccine MAP have shown comparable efficacy with conventional administration, and discussions about regulations for a vaccine MAP are underway. However, there are concerns of reasonable cost, mass production, efficacy, and safety standards that meet FDA approval, as well as the need for feedback regarding the best method of administration. Currently, microneedles have been studied for the delivery of many kinds of vaccines, and preclinical and clinical studies of vaccine microneedles are in progress. For the foreseeable future, some vaccines will continue to be administered with syringes and needles while the use of a vaccine MAP continues to be improved because of the advantages of less pain, self-administration, improved stability, convenience, and safety.